Achieving Net Zero Emissions Requires the Knowledge and Skills of the Oil and Gas Industry - Hastings, Astley; Smith, Pete (Frontiers in Climate, 2020)
The challenge facing society in the 21st century is to improve the quality of life for all citizens in an egalitarian way whilst at the same time decarbonizing anthropogenic activity to provide a safe global climate, limiting temperature rise to well below 2 º C with the aim is to limit the temperature 1.5 º C To do this the world must achieve net zero greenhouse gas (GHG) emissions by 2050. Currently spreading wealth and health across the globe is dependent on growing the GDP of all countries, driven by the use of energy, which until recently has mostly been derived from fossil fuel. Recently some countries have decoupled their GDP growth and greenhouse gas emissions through a rapid increases in low carbon energy generation. Considering the current level of energy consumption and projected implementation rates of low carbon energy production, a considerable quantity of fossil fuels is projected to be used to fill the gap and to avoid emissions of GHG and close the gap between the 1.5 º C carbon budget and projected emissions, carbon capture and storage (CCS) on an industrial scale will be required. In addition, the IPCC estimate that large scale GHG removal from the atmosphere is required to limit warming to below 2º C using technologies such as Bioenergy CCS, and direct carbon capture with CCS to achieve climate safety. In this paper we estimate the amount of carbon dioxide that will have to be captured and stored, the storage volume, technology and infrastructure required to achieve the energy consumption projections with net zero GHG emissions by 2050. We conclude that the oil and gas production industry alone has the geological and engineering expertise and global reach to find the geological storage structures and build the facilities, pipelines and wells required. Here we consider why and how oil and gas companies will need to morph from hydrocarbon production enterprises into net zero emission energy and carbon dioxide storage enterprises, decommission facilities only after CCS and thus be economically sustainable businesses in the long term, by diversifying in and developing this new industry.